2016
DOI: 10.4172/2329-891x.1000206
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Strongyloides Stercoralis Infection in Selected Tea Garden of Sylhet, Bangladesh

Abstract: Background: Strongyloidiasis infection is partially an asymptomatic infection and the diagnosis of patent infection is difficult using conventional parasitological methods. The residents of tea garden community of Sylhet, Bangladesh were robustly tested. Method:The collected stool samples were tested by Harada mori culture for the presence of larval stage of Strongyloides stercoralis and to reaffirm the same samples were subjected for conventional PCR, using primer sets deigned to amplify partial ribosomal DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…In the present study, the prevalence of S. stercoralis was 13.42%; higher in female (13.85%) than in male (11.77%) (t=1.57, p=0.36) (Figure 1) which is supported by Hossain et al (2016). Sultana et al (2015) conducted a coproanalysis among the slum dwellers of Dhaka and found higher prevalence of S. stercoralis in male (16.66%) than in female (11.32%).…”
Section: Sex Wise Prevalencesupporting
confidence: 76%
See 1 more Smart Citation
“…In the present study, the prevalence of S. stercoralis was 13.42%; higher in female (13.85%) than in male (11.77%) (t=1.57, p=0.36) (Figure 1) which is supported by Hossain et al (2016). Sultana et al (2015) conducted a coproanalysis among the slum dwellers of Dhaka and found higher prevalence of S. stercoralis in male (16.66%) than in female (11.32%).…”
Section: Sex Wise Prevalencesupporting
confidence: 76%
“…The lowest was observed in the summer (2.50%) (t=2.079, p=0.173) (Table 2) which is supported by another work (Ali-Shtayeh et al, 1989). A study conducted among the inhabitants of tea garden, Sylhet disclosed the winter season comprising the highest percentage of infection whereas rainy stood second; summer showed the lowest infection and researchers assumed that the variation of infection might be due to the environmental factors stimulating development of the larvae (Hossain et al, 2016).…”
Section: Seasonal Prevalencementioning
confidence: 99%
“…Males, people of white race, residents of chronic care institutions (Proctor et al, 1987) and people working with soil (such as person work in coal mines and farms) are at the greatest risk of acquiring this disease Keiser and Nutman, 2004). The seasonal distribution of Strongyloides infection was observed to be highest during rainy season (Hossain et al, 2016a;Hossain, 2015;Cook et al, 2009;Khanum et al, 2014) than summer and winter. During winter the environmental temperatures going low which arrest the development of rhabditiform larvae and continuation of free life cycle (Fauci, 2008).…”
Section: Risk Factors Host Factorsmentioning
confidence: 97%
“…Molecular and serological studies ensured its continuous existence in Bangladesh (Hossain et al, 2016a(Hossain et al, , 2016b(Hossain et al, , 2016cHall et al, 1994;Sultana et al, 2012). Severe complication with clumsy infection of strongyloidiasis may lead to substantial mortality as high as 87% (Ericsson et al, 2001).…”
Section: Introductionmentioning
confidence: 99%